Fecal microbiota transplantation from gestational diabetes mellitus patients induces glucose intolerance and subclinical inflammation in mice - Huang, Junhua; Yin, Xin; Zhang, Yujie; Zheng, Wei; Li, Guanghui (Frontiers in Microbiology, 2026)
BackgroundThe pathogenesis of gestational diabetes mellitus (GDM) is not fully understood, with gut microbiota dysbiosis emerging as a potential contributing factor. Existing animal models primarily mimic type 1 or type 2 diabetes, inadequately representing GDM. This study aimed to investigate whether fecal microbiota transplantation (FMT) from GDM patients is associated with the development of GDM-like phenotypes in mice, comparing this approach to traditional modeling methods.MethodsFecal microbiota from GDM patients and healthy controls were transplanted into antibiotic-treated pregnant mice, creating trimester-specific FMT models. Control groups included mice on a high-fat diet (HFD) and HFD combined with streptozotocin (STZ). Metabolic phenotypes were assessed via glucose and insulin tolerance tests, fasting blood glucose, and insulin measurements. Serum inflammatory markers were analyzed, and gut inflammation was evaluated. 16S rRNA sequencing was performed on key model groups.ResultsMice receiving FMT from mid-late trimester GDM donors or traditional treatments developed significant glucose intolerance, insulin resistance, and gestational weight gain. Serum levels of inflammatory factors (e.g., IL-1β, MMP-9) were elevated. 16S rRNA sequencing revealed markedly reduced gut microbiota diversity and increased Firmicutes/Bacteroidota ratio in both GDM-FMT and traditional model groups, with similar microbial community structures and alterations in metabolic and inflammation-related pathways.ConclusionGut microbiota from GDM patients may disrupt glucose homeostasis and contribute to a pro-inflammatory state during pregnancy. The GDM-FMT model effectively recapitulates key metabolic, inflammatory, and microbial dysbiosis features of GDM, providing a novel and reliable experimental tool for mechanistic studies.